2020
DOI: 10.1097/md.0000000000020516
|View full text |Cite
|
Sign up to set email alerts
|

Two treatment strategies for management of Neurosymptomatic cerebrospinal fluid HIV escape in Pune, India

Abstract: Symptomatic cerebrospinal fluid (CSF) viral escape (sCVE) is reported in people with HIV, who are on ritonavir-boosted protease inhibitor (PI/r) containing antiretroviral therapy (ART). Management of sCVE includes performing genotypic HIV-1 resistance testing (GRT) on CSF and plasma HIV and changing ART accordingly. Neither GRT nor newer drugs (Dolutegravir and Darunavir/ritonavir) are routinely available in India. As a result, management of sCVE includes 2 modalities: a) ART intensification by adding drugs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Our patient improved transiently after steroids, although steroids are not a standard treatment of CSF discordance. 7,15 Although our patient did not have neuropathologic confirmation of CD8 + encephalitis (diagnostic gold standard) because of resource limitations, his MRI showed T2 white matter hyperintensities as are reported in CD8 + encephalitis. 9 Steroids often improve CD8 encephalitis, so it is possible that our patient had an overlap of CSF discordance and CD8 encephalitis that improved with both steroids and optimization of his ART regimen.…”
Section: Discussionmentioning
confidence: 75%
“…Our patient improved transiently after steroids, although steroids are not a standard treatment of CSF discordance. 7,15 Although our patient did not have neuropathologic confirmation of CD8 + encephalitis (diagnostic gold standard) because of resource limitations, his MRI showed T2 white matter hyperintensities as are reported in CD8 + encephalitis. 9 Steroids often improve CD8 encephalitis, so it is possible that our patient had an overlap of CSF discordance and CD8 encephalitis that improved with both steroids and optimization of his ART regimen.…”
Section: Discussionmentioning
confidence: 75%
“…CSF viral escape did not develop even after months of ART suggesting that ART initiation at the early course of infection may help prevent the development of CSF viral escape [ 21 ]. Symptomatic CSF viral escape has also been reported in individuals on ART; one study showed that a switch to ARVs with a better CNS penetration effectiveness suppresses the HIV-1 VL and resolves the neurologic symptoms [ 44 ]. Lastly, we could not evaluate the impact of ART on compartmentalisation because almost half of the individuals on ART were recently initiated.…”
Section: Discussionmentioning
confidence: 99%
“…1) with deep brain nuclei involvement and enhancement in some patients [22,25]. Patients with symptomatic viral escape benefit from changes to ART regimens that provide better CNS penetration or to compensate for viral mutations [22,25,38]. Although similar clinical manifestations can occur in patients with secondary viral escape, these patients may benefit from therapies targeting the co-infection or steroids that help to control inflammation [39].…”
Section: Biotypes Of Hiv-associated Cognitive Impairmentsmentioning
confidence: 99%